Psycho-Social Support of Patients with Schizophrenia by Means of Their Autobiographical Memory (Psycho-Correctional and Psycho- Rehabilitational Aspects) - Bezsmertnyi, Oleksandr (Psychological Prospects Journal, 2015)
The article is devoted to the newest means of a psycho- social support of patients with paranoid schizophrenia, and the improvement of these patients’ postclinical adaptation to the life. The support envisages the use of a bio- psychosocial approach to generate further therapeutic cooperation in the ‘specialist– patient dyad on the post-clinical stage. The assistance is based on the autobiographical memory, personality psychological time, disease internal image, and mnestology paradigm of psychotherapy. The main goal is to provide a new set of psychodiagnostic, psychocorrectional, psychorehabilitational tools. With the help of psychodiagnostics routine aimed at assessing the quality of autobiographical memory and patient’s pathopersonology, the author identified the key principles of developing one rapid diagnostic technique instead of six. The analysis allowed us to identify adaptive features of personality deformed by mental disease. Adaptation deficit helped formulate the correction “targets”, to develop a system of correction and help patients overcome disease, which included psychocorrectional, educational, rehabilitational, and prevention practices. A multi-layer support system based on the resources of autobiographical memories was introduced into the male psychiatric ward. The majority of patients  who received the support, had a lower risk of recurrence of psychotic conditions, and demonstrated their emotional and motivational resources leveling conflicts and difficulties in micro- and macro-environment. Results show the significance and effectiveness of the designed means for further research and practice of psychologists, psychotherapists, social workers, mental health clinic doctors.